Pengaruh Content Marketing, Influencer Marketing, dan Brand Image terhadap Keputusan Pembelian Parfum Scarlett pada Generasi Z di Kota Semarang - Imayllina Auliya Putri; Amron Amron; Artha Febriana; Elia Resha Fatmawati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The development of social media encourages companies to untilize digital marketing strategies to influence consumer behavior, especially Generation Z who actively access product information online. This study aims to analyze the influencer of content marketing, influencer marketing and brand image on purchasing decisions for Scarlett parfume among Generation Z in Semarang City. This study uses a quantitative approach with data collection techniques through distributing questionnaires to 119 respondents selected using a purposivesampling method. The research data were analyzed using multiple linear regression supported by validity tests, reability tests, clasicial assumption tests, t- tests, F tests, and coefficients of determination. The result show that content marketing, Infleunce marketing, and Brand image have a positive and significant effect on purchasing decisions for Scarlett parfume. In addition, brand image is the most dominant variablein influence consumer purchasing decisions. Thecoefficient of determination (R²) value of 0.364 indicates that 36.4% of the variation in purchasing decisions can be explained by these three variables, while the remaining 63.6% is influenced by other factors outside theresearch model. These findings indicate that an effective digital marketing strategy through engaging content, credible influencer endorsment and a strong brand image can increase consumer interest and purchasing decisions towards Scarlett parfume product.